ANALISIS VARIABILITAS KULTIVAR JAGUNG PULUT (Zea mays Ceritina Kulesh) LOKAL SULAWESI TENGGARA - SAFUAN, LA ODE; BOER, DIRVAMENA; WIJAYANTO, TEGUH; SUSANTI, NELI (Jurnal Agroteknos, 2014)
The experiment was conducted in the Rahandouna village, Poasia, Kendari Southeast Sulawesi, from August to November 2013. The purpose of this study was to determine the estimate of heritability between characters of thirteen local waxy corn cultivars of Southeast Sulawesi. This study was prepared using a randomized block design (RBD), with 3 replicates. Total waxy corn cultivars studied was 13 species, so that there were 39 plots. Each plot consisted of a single cultivar. Observed variables were plant height (cm), stem diameter (cm), leaf area (cm2), number of leaves (strands), ear length (cm), cob diameter (cm), number of rows per ear, weight of 100 seeds (g), ear weight. The results of this study showed that there was narrow variability on all local waxy corn characters observed. Keywords: Local waxy corn, characters, cultivars, Southeast Sulawesi, variability